Penanaman Sikap Sopan Santun dalam Budaya Jawa pada Anak Usia Dini - M. Zidan Dermawan; Laely Khoerunnisa; Nurul Mubin (STIKes Ibnu Sina Ajibarang, 2025)
The aim of this research is to find out how Javanese culture instills noble character in early childhood. As library research, the approach uses qualitative research. The inability of today's children to speak politely shows that manners are now worse than before. The importance of paying attention to language politeness today. The Javanese language is currently almost extinct. The ngoko basis, the madyo krama basis, and the inggil krama basis are three unique linguistic levels of the Javanese language. Through the habituation and example of good Javanese language in daily life at home, school and society by adults, good manners in language will be developed in young children. In accordance with the principles of sasmita responsive (the ability to understand hidden meanings), andhap asor (humbling oneself while raising others), and karma (language style), the use of Javanese is appropriate and beneficial. In Javanese culture, these three cultural ideas are related to how to behave politely